2019
DOI: 10.1101/597732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel high-throughput molecular counting method with single base-pair resolution enables accurate single-gene NIPT

Abstract: Next-generation DNA sequencing is currently limited by an inability to count the number of input DNA molecules. Molecular counting is particularly needed when accurate quantification is required for diagnostic purposes, such as in single-gene non-invasive prenatal testing (sgNIPT) and liquid biopsy. We developed Quantitative Counting Template (QCT) molecular counting for reconstructing the number of input DNA molecules using sequencing data. We then used QCT molecular counting to develop sgNIPT of sickle cell … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These authors reported excellent performance, but it has the disadvantage of requiring samples from both parents and an affected child or sibling, as it is based on a linkage approach . Both of these papers described NIPD in pregnancies at known increased risk; however, 2019 saw the publication of two papers describing the screening of low‐risk pregnancies for monogenic disorders . These papers have been used to support at least three commercial companies launching platforms publicly available for screening pregnancies at general risk for monogenic disorders.…”
Section: Non‐invasive Prenatal Diagnosis and Screening For Monogenic mentioning
confidence: 74%
See 1 more Smart Citation
“…These authors reported excellent performance, but it has the disadvantage of requiring samples from both parents and an affected child or sibling, as it is based on a linkage approach . Both of these papers described NIPD in pregnancies at known increased risk; however, 2019 saw the publication of two papers describing the screening of low‐risk pregnancies for monogenic disorders . These papers have been used to support at least three commercial companies launching platforms publicly available for screening pregnancies at general risk for monogenic disorders.…”
Section: Non‐invasive Prenatal Diagnosis and Screening For Monogenic mentioning
confidence: 74%
“…The second publication also used an NGS‐based method for molecular counting to screen for sickle cell disease, cystic fibrosis, spinal muscular atrophy, alpha‐thalassemia, and beta‐thalassemia . The approach used in this report was to first screen the pregnant mothers' germline DNA, and the cfDNA in maternal plasma is reflex tested in mothers subsequently identified as carriers to determine the fetal genotype.…”
Section: Non‐invasive Prenatal Diagnosis and Screening For Monogenic mentioning
confidence: 99%